An institutional analysis of gender (in) equalities, covid-19 and governance of elite women's football in Australia, England and USA - Clarkson, B. G.; Parry, K. D.; Culvin, A.; Pope, S. (Sport, Business and Management, 2021)
Women`s football faces an existential threat in light of covid-19. Using case studies, we explore the covid-19 responses of three highly-ranked countries` national football associations (Australia, England, and USA) and their professional women`s football leagues to: (a) compare and shed new insights into the wide range of covid-19 responses, and (b) identify ways that other nations could successfully manage the tensions between the economic impact of covid-19 and their social and ethical responsibilities to women`s football. Drawing on institutional theory, a framework analysis was undertaken. 71 articles were examined to analyse the gendered global impacts that covid-19 is having on women`s football. The results highlight several important recommendations for nations to consider during the pandemic: (1) maintain active communication with the community to allay worries about the future of women`s football, (2) gather support from health and government officials, (3) seek out commercial and broadcasting partnerships to drive revenue, and (4) the interests of women`s football are best served when responsibility for the elite women`s league does not rest (solely) with national football associations. The study is first to explore institutional pressures and football governing bodies during covid-19 and provides a framework for other nations to manage major crises. A major question for the women`s football community emerged: should our expectations of gender equality in football shift in light of covid-19? We argue sport is an interwoven part of society and cannot be separated from gender equality issues.